CHANGES IN ERECTILE FUNCTION BEFORE AND AFTER PROSTATE BIOPSY - wibisono, Wibisono; Soebadi, Doddy Musbadianto; Alif, Sabilal; Pudjirahardjo, Widodo (Indonesian Journal of Urology, 2013)
Objective: To evaluate erectile function before and after transrectal ultrasound (TRUS) guided prostate biopsy using International Index of Erectile Function-5 (IIEF-5) and Erection Hardness Score (EHS) instrument. Material & Method: We conducted a study on 17 BPH LUTS patients who underwent TRUS guided prostate biopsy from January to April 2011 in Urological Minimal Invasive Installation (IIU) Dr. Soetomo Hospital. Out of 17 patients, three patients had mild ED, while 14 other patients had normal erectile function before the procedure. After TRUS guided prostate biopsy, we performed erectile function assessment using the IIEF-5 and EHS at weeks I, II, and IV. Results: Pathological examination of all specimens from prostate biopsy results revealed BPH. There were 2 patients with hematuria and 1 patient with rectal bleeding shortly after the biopsy, which resolved spontaneously less than 24 hours. Based on the IIEF-5 there were 4 patients (23,5%) with decreased erectile function in the evaluation of first week after prostate biopsy, and it reduced to 2 patients (11,7%) whose erectile function was still decreasing in the evaluation week II, while in fourth week evaluation there was 1 patient (5,9%) with decreased erectile function. Based on EHS data obtained, there were 5 patients (29,4%) with decreased scores in evaluations week II, and in the evaluation of week IV there were no patients having erectile function problems compared with EHS data before prostate biopsy. Conclusion: TRUS guided prostate biopsy can have temporary effect on erectile function.Keywords: Erectile dysfunction, prostate biopsy, international index of erectile function-5, erection hardness score.